Phenotype variability of neural crest derived tumours in six Italian families segregating the same founder SDHD mutation Q109X. Issue 8 (1st August 2005) - Simi, L; Sestini, R; Ferruzzi, P; Gaglianò, M S; Gensini, F; Mascalchi, M; Guerrini, L; Pratesi, C; Pinzani, P; Nesi, G; Ercolino, T; Genuardi, M; et al.
Abstract : Background: Mutations in genes coding for the mitochondrial complex II succinate dehydrogenase (SDH) subunits cause familial neural crest derived (NCD) tumours. Methods: Index cases from six apparently unrelated families affected by NCD tumours were analysed for mutations in the SDHB, SDHC, and SDHD genes. Results: The same nonsense germline heterozygous mutation (Q109X) in exon 4 of the SDHD gene was found in each of the six families. Overall, 43 heterozygotes were identified. These were evaluated for the presence of NCD tumours through radiological examination of the neck, thorax, and abdomen, and measurement of urinary metanephrines and plasma chromogranin A. A novel missense SDHD variant, T112I, which did not segregate with the Q109X mutation and was not associated with phenotypic manifestations, was observed in one of the families. Microsatellite analysis showed a common haplotype in all individuals heterozygous for the Q109X mutation, indicating a founder effect. Overall, 18 heterozygotes were clinically affected by at least one NCD tumour. Every affected patient inherited the germline mutation from the father, confirming SDHD maternal genomic imprinting. Penetrance of the paternally inherited mutation progressively increased from 33% to 83% at 30 and 60 years, respectively. Affected patients showed high clinical variability, ranging from monolateral to bilateral glomus tumours variably associated or not with paragangliomas or phaeochromocytomas. Loss of heterozygosity was observed in tumour cells isolated by laser capture microdissection. Conclusions: This study shows that a single founder SDHD mutation is present in an area of central Italy and that this mutation is associated with widely variable interfamilial and intrafamilial expressivity.